Dolutegravir efficacy at 48 weeks in key subgroups of treatment-naive HIV-infected individuals in three randomized trials. (14th January 2015) - Raffi, François; Rachlis, Anita; Brinson, Cynthia; Arasteh, Keikawus; Górgolas, Miguel; Brennan, Clare; Pappa, Keith; Almond, Steve; Granier, Catherine; Nichols, W. Garrett; Cuffe, Robert Liam; Jr, Joseph Eron; et al.
<x xml:space="preserve">Abstract</x> Objectives: Dolutegravir (DTG) has been studied in three trials in HIV treatment-naive participants, showing noninferiority compared with raltegravir (RAL), and superiority compared with efavirenz and ritonavir-boosted darunavir. We explored factors that predicted treatment success, the consistency of observed treatment differences across subgroups and the impact of NRTI backbone on treatment outcome. Design: Retrospective exploratory analyses of data from three large, randomized, international comparative trials: SPRING-2, SINGLE, and FLAMINGO. Methods: We examined the efficacy of DTG in HIV-infected participants with respect to relevant demographic and HIV-1-related baseline characteristics using the primary efficacy endpoint from the studies (FDA snapshot) and secondary endpoints that examine specific elements of treatment response. Regression models were used to analyze pooled data from all three studies. Results: Snapshot response was affected by age, hepatitis co-infection, HIV risk factor, baseline CD4+ cell count, and HIV-1 RNA and by third agent. Differences between DTG and other third agents were generally consistent across these subgroups. There was no evidence of a difference in snapshot response between abacavir/lamivudine (ABC/3TC) and tenofovir/emtricitabine (TDF/FTC) overall [ABC/3TC 86%, TDF/FTC 85%, difference 1.1%, confidence interval (CI) −1.8, 4.0 percentage points, P = 0.61] or at high viral loads (difference −2.5, 95% CI −8.9, 3.8 percentage points, P = 0.42). Conclusions: DTG is a once-daily, unboosted integrase inhibitor that is effective in combination with either ABC/3TC or TDF/FTC for first-line antiretroviral therapy in HIV-positive individuals with a variety of baseline characteristics.